The behavior of superconducting gaps in a two-band model of HTSC - Konsin, P.; Kristoffel, N.; Rubin, P. (Физика низких температур, 1996)
The carrier concentration and temperature dependences of superconducting gaps are calculated for La₂₋xSrxCuO₄ and Y₁Ba₂Cu₃O₇-y in a two-band model. The ratios 2|Δ₁,₂ (0)/kBTc show peculiarities as a function of the carrier concentration. Temperature dependences of superconducting gaps are of the BCS type.